2020
DOI: 10.3390/ijerph17249510
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries among Refugees in Europe: A Systematic Literature Review

Abstract: Oral health is one of the most neglected aspects of refugee health. The study aimed to systematically review evidence on prevalence of dental caries and dental care services provided to refugees in Europe. Following PRISMA guidelines, we searched PubMed, Cochrane, WHOLIS, Web of Science, Medline Ovid, and Google Scholar identifying studies on dental caries among refugees in Europe after the 2015 refugee crisis. From 3160 records, fourteen studies were included in the analysis. Eight studies on oral health show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…This compared favourably with dental visits among the general populations in Australia [29]. Whereas these ndings are encouraging, considering the higher burden of dental disease among refugee males and children compared to those in general population [33], a higher uptake among these groups would have been expected. In refugee families, the dental health-related attitude of parents is critical in determining their children's utilisation pattern, as they are the decision-makers for their children's dental care needs [34].…”
Section: Discussionmentioning
confidence: 87%
“…This compared favourably with dental visits among the general populations in Australia [29]. Whereas these ndings are encouraging, considering the higher burden of dental disease among refugee males and children compared to those in general population [33], a higher uptake among these groups would have been expected. In refugee families, the dental health-related attitude of parents is critical in determining their children's utilisation pattern, as they are the decision-makers for their children's dental care needs [34].…”
Section: Discussionmentioning
confidence: 87%
“…The results of this study clearly shows that refugees have very poor oral health status, as the average number of DMFT was (8.3) which is much higher than the normal value recommended by world health organization which is lower than (3) (24). And also, the average number of DMFT among children was high in age group (1-5 years), and in age group (6)(7)(8)(9)(10)(11)(12) as it was (5.47, 5.62) retrospectively. This number is higher compared to the population in the original countries, for example, a study published in 2019 found that internally displaced Syrian children had on average (3.36) for the DMFT value (25), while another publication from Al-Zaatari refugee camp in Jordan found that children had an average DMFT number of (3.64) (14).…”
Section: Demographic Data and Sample Analysismentioning
confidence: 85%
“…Oral health and dental treatment are considered secondary needs in humanitarian context despite the sever pain caused from oral sources and the huge impact on overall health and quality of life (10,11), research articles from refugee camps in different countries reported bad oral health and increased rate of pain from dental sources among refugees (12), and negative impact of the bad oral health on the quality of life (10), and refugees in the camps might suffer from pain for weeks before they are able to access dental treatment services (13), and one study concluded that refugees in Zaatari camp in Jordan have high level of dental needs which is not met (14), and oral health among refuges is often worse than the general oral health of the population of any host country (15), therefore oral health remain a major concern among refugees living for long term in camps which is until now not taking enough care and consideration (16). This research focusses on the oral health and dental treatment provided for refugees in the medical area inside Karatepe camp in Lesvos.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study assessing the OHQoL of refugees in settlements in Northern Greece. A systematic review of dental services for refugees in Europe by Bhusari et al 16 reported that there were more data on the general health of refugees than OH data.…”
Section: Discussionmentioning
confidence: 99%